Expression and Functional Characterization of Choline Transporter in Human Keratinocytes - Yoshihiro Uchida; Masato Inazu; Hiroshi Takeda; Tomoko Yamada; Hirohisa Tajima; Teruhiko Matsumiya (Elsevier, 2009)
Choline is essential for synthesis of the major membrane phospholipid phosphatidylcholine. Moreover, it serves as a precursor for synthesis of the neurotransmitter acetylcholine (ACh). Keratinocytes of the epidermis synthesize and release ACh. The uptake of choline is the rate-limiting step in both ACh synthesis and choline phospholipid metabolism, and it is a prerequisite for keratinocyte proliferation. However, the nature of the choline transport system in keratinocytes is poorly understood. In this study, we examined the molecular and functional characterization of choline uptake into cultured human keratinocytes. Choline uptake into keratinocytes was independent of extracellular Na+, saturable, and mediated by a single transport system with an apparent Michaelis-Menten constant of 12.3 μM. Choline uptake was reduced when the keratinocyte membrane potential was depolarized by high K+. These results provide evidence that the choline transport activity is potential-sensitive. Various organic cations inhibit the choline transport system. RT-PCR demonstrated that keratinocytes expressed mRNA for choline transporter-like protein 1 (CTL1), mainly the CTL1a subtype. The present biochemical and pharmacological data suggest that CTL1a is functionally expressed in human keratinocytes and is responsible for the uptake of choline and organic cations in these cells. Keywords:: choline, acetylcholine, transporter, keratinocyte, cell proliferation